On the conceptual issues of the application of modern information and communication technologies in the civil process - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2022)
The article deals with the conceptual issues of modern information technologies using in the civil process. In particular, the author explores the prerequisites for the introduction of these technologies in legal proceedings, analyses the acceptability of the terms «electronic litigation», «electronic justice», «electronic court», classifies information technologies through the prism of procedural phenomena (concepts, categories). The classification of information technologies is carried out according to different criteria (depending on the categories of subjects of the process, the method of interaction with procedural information, the segments of legal proceedings, the complexity of the case, the stage of the process, the consequences of the violation, etc.), while showing the practical significance of each of classifications. On this basis, the work made a lot of proposals for improving the procedural legislation and the practice of its application.
Keywords: civil process; information and communication technologies; electronic justice; electronic litigation; electronic court; Internet; videoconferencing; court notices; electronic evidence; fixing the progress of the process; grounds for annulment of judgments